2015
DOI: 10.1063/1.4914116
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of nanoscale V-pits to optimize internal quantum efficiency of InGaN multiple quantum wells

Abstract: We systematically investigated the influence of nanoscale V-pits on the internal quantum efficiency (IQE) of InGaN multiple quantum wells (MQWs) by adjusting the underlying superlattices (SLS). The analysis indicated that high barrier energy of sidewall MQWs on V-pits and long diffusion distance between the threading dislocation (TD) center and V-pit boundary were crucial to effectively passivate the non-radiative centers of TDs. For a larger V-pit, the thicker sidewall MQW on V-pit would decrease the barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 23 publications
5
46
0
Order By: Relevance
“…6(b), which has a good agreement with the experiments. 14,21 With regard to the irregular distribution of TDs in the real epi-layers, the TD density we used is an averaging number. To discuss the influence of TD densities for the overall LED performance, we further simulated 1.0×10 8 cm −2 and 6.25×10 8 cm −2 TD densities, which are corresponding to 1 µm × 1 µm and 700 nm × 700 nm simulation area, respectively.…”
Section: -7mentioning
confidence: 99%
See 2 more Smart Citations
“…6(b), which has a good agreement with the experiments. 14,21 With regard to the irregular distribution of TDs in the real epi-layers, the TD density we used is an averaging number. To discuss the influence of TD densities for the overall LED performance, we further simulated 1.0×10 8 cm −2 and 6.25×10 8 cm −2 TD densities, which are corresponding to 1 µm × 1 µm and 700 nm × 700 nm simulation area, respectively.…”
Section: -7mentioning
confidence: 99%
“…20 The influence of V-pit diameters on the efficiency is also discussed by PL measurements. 21 In addition, the atom probe tomography (APT) data indicates that the structure of QWs in V-pit regions is deformed, where the geometry is adjusted, and the width and indium composition of inclined sidewall QWs in V-pits are especially thinner and lower. 22 Moreover, experiments demonstrated that the energy barriers between lateral and sidewall QWs are depending on the V-pit diameter and tried to explain the PL radiative efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On top of the n-GaN layer are 60 pairs of superlattice layers (SLs), which assist the V-pits formation along the TDs. The final layer consists of an InGaN/GaN multi-quantum wells (MQWs) active layer23. There are two groups of quantum wells, each with a different indium composition.…”
Section: Methodsmentioning
confidence: 99%
“…The growth rate of the (1 1 0 1) face was much slower than on the c-plane, the growth rate ratio between the smipolar and c-plane was around 0.1-0.2. The growth rate of semipolar InGaN MQWs on the GaN nanopyramid is significantly influenced by the scale factor of growth condition [22,23]. According to EDS results, the Gallium and Indium element mapping images of the GaN nanopyramid also exhibit high Indium content on c-plane InGaN/GaN NHDs as shown in Fig.…”
mentioning
confidence: 88%